Implikasi Pendidikan dari Qs An-Nisa ayat 58 tentang Amanah dan Adil terhadap Kepemimpinan dalam Pendidikan - Ikhwan Abdian; Mulyani, Dewi (Bandung Conference Series: Islamic Education, 2024)
Abstract. The Great Qur'an is guidance, a legal constitution, a source of God's system of rules for life, a path to becoming a leader of an educational institution that is approved by Allah, a source of wisdom, trustworthy and fairness for humans. This research uses this research method, which is more of a qualitative descriptive analytical research approach (literature study) equipped with data sources in this research, namely primary data sources, the Qur'an and Hadith and secondary data sources, namely books that discuss leadership in education. These books are intended as tools to help analyze the interpretation of the Tafsir Al-Qur'an regarding verses relating to leadership in education. Data collection techniques collected in this research used library research methods. The collection technique is by searching for sources such as tafsir, books, journals and existing research to determine literature related to the verse being researched through the tafsir method to analyze QS An-Nisa verse 58 which is associated with leadership in education. Allah commanded to convey the mandate to lead educational institutions to those who are entitled to receive it (an-tuaddul amanati ila Ahliha), Allah Swt also ordered the elected leaders of educational institutions to establish laws fairly (hakamtum bainannas an tahkumu bil adl). In this verse, according to the mufassir, the meaning of amanati ila Ahliha means a form of handover, entrustment to those who are experts in their field and hakamtum means a sign of establishing a comprehensive law. and bil adli can be interpreted as a whole as Fair, namely establishing the law correctly. Abstrak. Al-Qur'an yang Agung adalah petunjuk hidayah, konstitusi hukum, sumber sistem aturan Tuhan untuk kehidupan, jalan untuk menjadi seorang Pemimpin lembaga pendidikan yang diridhoi oleh allah, sumber hikmah, kebenaran, dan keadilan bagi manusia. Penelitian ini memakai Metode penelitian ini adalah lebih kepada penelitian kualitatif deskriptif analitis dengan pendekatan (studi literatur) dengan dilengkapi sumber data dalam penelitian ini yaitu sumber data primer al-qur’an dan hadits dan sumber data sekunder yaitu buku-buku yang membahas tentang kepemimpinan dalam pendidikan. Buku-buku tersebut dimaksudkan sebagai alat unuk membantu menganalisis penafsiran Tafsir al-qur’an terhadap ayat-ayat yang berkaitan dengan kepemimpinan dalam pendidikan. Teknik Pengumpulan data yang dikumpulkan pada penelitian ini menggunakan metode penelitian kepustakaan (library research). Teknik pengumpulan dengan cara mencari sumber seperti tafsir, buku, jurnal, dan riset-riset yang sudah ada untuk menentukan literatur yang berkaitan dengan ayat yang diteliti melalui metode tafsir untuk menganalisis QS An-Nisa ayat 58 yang dikaitkan dengan kepemimpinan dalam pendidikan. Allah memerintahkan untuk menyampaikan amanat memimpin lembaga pendidikan kepada yang berhak menerimanya (an-tuaddul amanati ila ahliha), Allah Swt juga memerintahkan kepada pemimpin lembaga pendidikan yang terpilih agar menetapkan hukum dengan adil (hakamtum bainannas an tahkumu bil adl). Dalam ayat ini, menurut para mufassir menjelaskan makna amanati ila ahliha artinya berupa bentuk penyerahan, titipan kepada yang ahli dibidangnya dan hakamtum berarti sebuah isyarat menetapkan hukum yang menyeluruh. dan bil adli dapat diartikan secara menyeluruh adalah dengan Adil yaitu menetapkan hukum dengan benar.